Crimean-Congo haemorrhagic fever virus in Kazakhstan (1948-2013). (September 2015) - Nurmakhanov, Talgat; Sansyzbaev, Yerlan; Atshabar, Bakhyt; Deryabin, Pavel; Kazakov, Stanislav; Zholshorinov, Aitmagambet; Matzhanova, Almagul; Sadvakassova, Alya; Saylaubekuly, Ratbek; Kyraubaev, Kakimzhan; Hay, John; Atkinson, Barry; et al.
Highlights: Comprehensive summary of CCHF diagnosis and detection in Kazakhstan. Review of current endemic areas, incidence of disease and epidemiology. Data for confirmed cases of CCHF since first identification in Kazakhstan in 1948 through to 2013. Abstract: Crimean-Congo haemorrhagic fever (CCHF) is a pathogenic and often fatal arboviral disease with a distribution spanning large areas of Africa, Europe and Asia. The causative agent is a negative-sense single-stranded RNA virus classified within the Nairovirus genus of the Bunyaviridae family. Cases of CCHF have been officially recorded in Kazakhstan since the disease was first officially reported in modern medicine. Serological surveillance of human and animal populations provide evidence that the virus was perpetually circulating in a local enzoonotic cycle involving mammals, ticks and humans in the southern regions of the country. Most cases of human disease were associated with agricultural professions such as farming, shepherding and fruit-picking; the typical route of infection was via tick-bite although several cases of contact transmission associated with caring for sick patients have been documented. In total, 704 confirmed human cases of CCHF have been registered in Kazakhstan from 1948-2013 with an overall case fatality rate of 14.8% for cases with a documented outcome. The southern regions of Kazakhstan should be considered endemic for CCHF with cases reported from these territories on an annual basis. Modern diagnostic technologies allow for rapid clinical diagnosis and for surveillance studies to monitor for potential expansion in known risk areas.